Adolescent care: Part 1: Are family physicians caring for adolescents’ mental health? - Gilbert, Andrée (College of Family Physicians of Canada, 2006)
OBJECTIVE: To investigate how often family physicians see adolescents with mental health problems and how they manage these problems. DESIGN: Mailed survey completed anonymously. SETTING: Province of Quebec. PARTICIPANTS: All 358 French-speaking family physicians who practise primarily in local community health centres (CLSCs), including physicians working in CLSC youth clinics, and 749 French-speaking practitioners randomly selected from private practice. MAIN OUTCOME MEASURES: Frequency with which physicians saw adolescents with mental health problems, such as depression, suicidal thoughts, behavioural disorders, substance abuse, attempted suicide, or suicide, during the last year or since they started practice. RESULTS: Response rate was 70%. Most physicians reported having seen adolescents with mental health problems during the last year. About 10% of practitioners not working in youth clinics reported seeing adolescents with these disorders at least weekly. Anxiety was the most frequently seen problem. A greater proportion of physicians working in youth clinics reported often seeing adolescents for all the mental health problems examined in this study. Between 8% and 33% of general practitioners not working in youth clinics said they had not seen any adolescents with depression, behavioural disorders, or substance abuse. More than 80% of physicians had seen adolescents who had attempted suicide, and close to 30% had had adolescent patients who committed suicide. CONCLUSION: Family physicians play a role in adolescent mental health care. The prevalence of mental health problems seems higher among adolescents who attend youth clinics. Given the high prevalence of these problems during adolescence, we suggest on the basis of our results that screening for these disorders in primary care could be improved.